(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
The application of natural plant-derived dyes to replace ruthenium-based material as photo-absorber in solar cells application, have been extensively studied. Several advantages such as low cost, abundant in supply, sustainability and environmentally-safe make natural materials as current favourite photo-absorber. Natural plant-derived dyes are known containing natural compounds (e.g. carotenoids, chlorophylls, anthocyanins) that have the characteristics of electronic delocalization in extended ?-orbital system involving in electronic transfer mechanism. To date, massive investigations were done to exploit this system to be used as a potential photo-absorber in solar cells. Due to this matter, the hybrid dyes from the mixture of Pandanus amaryllifolius (pandan, P) and Curcuma longa (turmeric, T) were successfully prepared and several physical characterizations were carried out to analyse the photo-absorber (sensitizer) properties. From the results obtained, the ratios of P:T was varied into 1:2, 1:4, 4:1, and 8:1. This ratio has changed the wavelength of absorbers that were slightly shifted and the indirect bandgap (Eg) also were significantly changed. With this new approach, the bandgap of the hybrid dyes as core point in modulating electrical conductivity of photo-absorber can be simply tuned. By implying two different extract dyes to form hybrid dyes, the bandgap was found decreased with higher ratio of T used. Overall results suggesting that by adjusting the ratio of hybrid dyes, the photo-absorber properties and the Eg values were differed and with slightly modification, better electrical conductivity can be expected for solar cells application.